Nasal mucociliary clearance in subjects with COPD after smoking cessation - Ito, Juliana T. [UNESP]; Ramos, Dionei [UNESP]; Lima, Fabiano F. [UNESP]; Rodrigues, Fernanda M. M. [UNESP]; Gomes, Paulo R.; Moreira, Graciane L.; Macchione, Mariangela; Toledo, Alessandra C.; Ramos, Ercy M. C. [UNESP] (Daedalus Enterprises Inc, 2015)
BACKGROUND: Exposure to cigarette smoke causes significant impairment in mucociliary clearance (MCC), which predisposes patients to secretion retention and recurrent airway infections that play a role in exacerbations of COPD. To determine whether smoking cessation may influence MCC and frequency of exacerbations, the following groups were evaluated: ex-smokers with COPD, smokers with COPD, current smokers with normal lung function, and nonsmokers with normal lung function. METHODS: Ninety-three subjects were divided into 4 groups: ex-smokers with COPD (n = 23, 62.4 +/- 8.0 y, 13 males), smokers with COPD (n = 17, 58.2 +/- 8.0 y, 6 males), current smokers (n = 27, 61.5 +/- 6.4 y, 17 males), and nonsmokers (n = 26, 60.8 +/- 11.3 y, 7 males). MCC was evaluated using the saccharin transit time (STT) test, and the frequency of exacerbations in the last year was assessed by questionnaire. The Kruskal-Wallis test followed by Dunn's test were used to compare STT among groups, and the Goodman test was used to compare the frequency of exacerbations. RESULTS: STT of smokers with COPD (16.5 [11-28] min; median [interquartile range 25-75%]) and current smokers (15.9 110-271 min) was longer compared with ex-smokers with COPD (9.7 [6-12] min) and nonsmokers (8 [6-16] min) (P < .001). There was no difference in STT values between smokers with COPD and current smokers, and these values in ex-smokers with COPD were similar to the control group (P > .05). The frequency of exacerbations was lower in ex-smokers with COPD compared with smokers with COPD. CONCLUSIONS: One year after smoking cessation, subjects with COPD had improved mucociliary clearance.
Keywords: Chronic obstructive pulmonary disease; Smoking; Mucociliary clearance; Disease exacerbation; Smoking cessation; Respiratory infections